The Effect of Chitosan Extracted from Green Mussel Shells Perna viridis on Sonneratia caseolaris Mangrove Syrup Preservation - Muhammad Sholahuddin Al Ayyubi; Farikhah Farikhah; Nur Maulida Safitri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Green mussels (Perna viridis) are one of the prospective aquatic resources that can be developed into a high-value commodity. Their shells, on the other hand, are rarely used and discarded; despite the fact that the shells are contain chitosan, which can be used as a food preservative.The purpose of this study is to examine the effect of chitosan administration from green mussel shells on Sonneratia caseolaris mangrove syrup at various concentrations. The experimental design used Completely Randomized Design (CRD) with 7 treatments within 3 replications. The study lasted 30 days in order tho find the best concentration of chitosan as a preservative. The McFarland method was used to evaluate the total dissolved density (Brix), the acidity (pH), the organoleptic study (aroma and color), and the bacterial density. The following treatments were used in this study: P1 to P5 (the addition of 0.1-0.5 ml of green mussel sheel chitosan solution); P6 (the negative control or without the addition of green mussel shell chitosan solution); and P7 (the positive control with the addition of 0.1 ml sodium benzoate (C7H5NaO2) as commercial preservative). The results showed that the average value of total dissolved density P1-P7 varied between 22-22.46 (Brix); acidity (pH) of P1-P7 ranged between 2-3,1; and the organoleptic test obtained points 5 (neutral) on the aroma and color test. As a conclusion, chitosan derived from green mussel shellsP. viridis is promising agent to be utilized as a preservative in S. caseolaris mangrove syrup.